ANALISIS VARIABEL-VARIABEL FUNDAMENTAL YANG BERPENGARUH TERHADAP PRICE EARNING RATIO SEBAGAI DASAR PENILAIAN SAHAM (Studi Pada Saham-Saham indeks LQ 45 di Bursa Efek Jakarta) - Yulianti - -; Atim - Djazuli; S.M. Kiptiyah - - (Wacana Journal of Social and Humanity Studies, 2009)
ABSTRACT   The existence of the Indonesian Capital Market is very important for Indonesian economic activity, due to the fact that capital market development is one indicated of the betterment of national economy. In terms of investment, capital market development is determined by the economic fundamentals, public company performance, and investor’s tendency to invest. Stock, being the main investment object, offers several preferences to choose by the investor, one of which is LQ 45 stock indices. The Jakarta Stock Exchange (JSX) focus is put on the trade of LQ 45 stock indices. Therefore, it is necessary to evaluate the LQ 45 stock indices by taking into account the four main variables as suggested by the Gordon model. In line with the above, this study concerns stock evaluation based on the fundamental analysis by the price earning ratio approach. Explanatory variable is dividend payout ratio, return on equity, earning growth and financial leverage, dependent variable is price earning ratio. Purposive random sampling and multiple regression using 16 emittent of LQ 45 stock indices samples were used]. The aims of this research is to know the influence of the fundamental variables on the price earning ratio, and the naturalness of LQ 45 stock indices value. The samples used are the big, established and stable companies included in  calculation of LQ 45 indices, and thus would not apply to non LQ 45 indices at the JSX from 1999 through 2000. The results of the study indicate that (1) out of the four explanatory variables used: dividend payout ratio, return on equity, earning growth and financial leverage whereas simultaneously, all the variables showed significant influence; (2) dividend payout ratio was the most significant explanatory variable influencing the price earning ratio; (3) based on the price earning ratio analysis, no natural value was evidence of LQ 45 stock indices at the JSX.   Keywords: Price Earning Ratio as Bases in Stock Valuation